2020
DOI: 10.3390/ijerph17144926
|View full text |Cite
|
Sign up to set email alerts
|

“A Woman Is a Puppet.” Women’s Disempowerment and Prenatal Anxiety in Pakistan: A Qualitative Study of Sources, Mitigators, and Coping Strategies for Anxiety in Pregnancy

Abstract: Common mental disorders are highly prevalent among pregnant women in low- and middle-income countries, yet prenatal anxiety remains poorly understood, particularly in the sociocultural context of South Asia. Our study explored sources, mitigators, and coping strategies for anxiety among symptomatic pregnant women in Pakistan, particularly in relation to autonomy in decision-making and social support. We interviewed 19 pregnant married women aged 18–37 years recruited from 2017–2018 at a public hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 60 publications
0
16
0
2
Order By: Relevance
“…In rural and traditional families in Pakistan, women are usually not allowed to go alone to seek health care. They remain dependent on their husband, or elder family members for going outside of home to visit relatives, shopping and seeking health care [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In rural and traditional families in Pakistan, women are usually not allowed to go alone to seek health care. They remain dependent on their husband, or elder family members for going outside of home to visit relatives, shopping and seeking health care [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…al. found gender norms to be a major cause of constrained agency, decision-making, and prenatal anxiety amongst pregnant women [9]).…”
Section: Discussionmentioning
confidence: 99%
“…Coping refers to “constantly changing cognitive and behavioral efforts to manage specific external and/or internal demands that are appraised as taxing or exceeding the resources of the person” (Lazarus and Folkman 1984 , p. 141). Seeking and receiving social support to assist with coping is well-known to mitigate the effects of distress experienced during the perinatal period (Ibrahim et al 2019 ; Khatri et al 2019 ; Rowther et al 2020 ). Social support network size, satisfaction with close relationships, and degree of social involvement can all act as buffers against stress and its negative impacts (Goletzke et al 2017 ; Taubman-Ben-Ari 2019 ) and are identified as a key resource to reduce stress during pregnancy (Bloom et al 2012 ; Rowther et al 2020 ).…”
Section: Prenatal Mental Health and Coping Strategiesmentioning
confidence: 99%
“…Seeking and receiving social support to assist with coping is well-known to mitigate the effects of distress experienced during the perinatal period (Ibrahim et al 2019 ; Khatri et al 2019 ; Rowther et al 2020 ). Social support network size, satisfaction with close relationships, and degree of social involvement can all act as buffers against stress and its negative impacts (Goletzke et al 2017 ; Taubman-Ben-Ari 2019 ) and are identified as a key resource to reduce stress during pregnancy (Bloom et al 2012 ; Rowther et al 2020 ). An important facet of social support is the degree to which one’s preferred type of social support is accessible at the time it is needed most (Leahy-Warren et al 2018 ).…”
Section: Prenatal Mental Health and Coping Strategiesmentioning
confidence: 99%